Lysine 58-cleaved β2-microglobulin is not detectable by 2D electrophoresis in ex vivo amyloid fibrils of two patients affected by dialysis-related amyloidosis - Giorgetti, Sofia (Cold Spring Harbor Laboratory Press, 2007)
The lysine 58 cleaved and truncated variant of β(2)-microglobulin (ΔK58-β2m) is conformationally unstable and present in the circulation of a large percentage of patients on chronic hemodialysis, suggesting that it could play a role in the β2-microglobulin (β2m) amyloid fibrillogenesis associated with dialysis-related amyloidosis (DRA). However, it has yet to be detected in the amyloid deposits of such patients. Here, we extracted amyloid fibrils, without denaturation or additional purification, from different amyloidotic tissues of two unrelated individuals suffering from DRA, and characterized them by high-sensitivity bidimensional gel electrophoresis (2D-PAGE), immunoblotting, MALDI time-of-flight mass spectrometry, and protein sequencing. To confirm whether or not this species could be identified by our proteomic approaches, we mapped its location in 2D-PAGE, in mixtures of pure ΔK58-β2m, and extracts of amyloid fibrils from patients, to a discrete region of the gel distinct from other isoforms of β2m. Using this approach, the two known principal isoforms found in β2m amyloid were identified, namely, the full-length protein and the truncated species lacking six N-terminal amino acid residues (ΔN6-β2m). In contrast, we found no evidence for the presence of ΔK58-β2m.